Dominasi Patriarki dalam Novel La Barka Karya N.H Dini dan Nayla - Katharina Woli Namang; Nur Sakinah Natalia Mercyana; Fransiska Andrea Poa; Elisabeth Gustina Nesti; Yoseph Hendra; Magdalena Nona Irmin (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This research aims to describe the portrait of women from the perspective of patriarchal culture who are always considered to be in an inferior position, and experience various acts of discrimination in the domestic and public spheres. These acts of discrimination take the form of marginalization, subordination and repression which are represented by female characters in the literary works La Barka and Nayla. The type of research used is qualitative descriptive research. This research uses a feminist literary criticism approach. The data in this research is in the form of exposure to words, sentences, dialogue and helping which reflect patriarchal domination in the form of marginalization, subordination and repression experienced by the female characters in La Barka and Nayla. The data source in this research is the literary work entitled La Barka by Nh. Dini and Nayla by Djenar Maesa Ayu. Based on the results of data analysis and research findings, it was concluded that in La Barka and Nayla data was found regarding (1) patriarchal domination in the form of marginalization, (2) patriarchal domination in the form of subordination, and (3) patriarchal domination in the form of repression.